Translational and Clinical Significance of DAMPs, PAMPs, and PRRs in Trauma-induced Inflammation - Rai, Vikrant; Mathews, Gillian; Agrawal, Devendra K (Archives of Clinical and Biomedical Research, 2022)
Increased morbidity and mortality after polytrauma due to multiple organ failure (MOF) is a major concern for clinicians. Systemic inflammatory response syndrome (SIRS) and sepsis are the major underlying causes. Damage-associated molecular proteins (DAMPs) released after polytrauma induce an inflammatory immune response to repair the tissue, however, persistent inflammation finally results in immunosuppression and MOF. During immunosuppression, additional exposure of the traumatized tissue to pattern-associated molecular patterns (PAMPs) further adds to the continuum of inflammatory cascade causing sepsis. These two hits worsen the condition of the patient and increase morbidity and mortality. Thus, it is critical to stratify the patient based on trauma severity and inflammatory biomarkers levels and design treatment accordingly for a better clinical outcome. Although some of the molecular mechanisms involved in SIRS and MOF after polytrauma have been reported, there is limited information on the critical factors related to the study of DAMPs and PAMPs, including the timing of sampling (time elapsed after trauma), source of sampling (blood, urine, saliva), proteomics and metabolomics, multiplex plasma assay, comparative interpretation of the results from various sources and diagnostic value, and interpretation on the translational and clinical significance. Additionally, there is limited literature on DAMPs like heat shock proteins, mitochondrial DNA, neutrophil extracellular traps, and their role in SIRS and MOF. Further, it is also important to distinguish between the biomarkers of SIRS and sepsis in a time-bound window to have a better clinical outcome. This critical review focuses on these aspects to provide comprehensive information and thought-provoking discussion to design future investigation and clinical trials.